Evaluation of the feasibility and sustainability of the joint human and animal vaccination and its integration to the public health system in the Danamadji health district, Chad - Mahamat Fayiz Abakar; Djimet Seli; Filippo Lechthaler; Lisa Crump; Arielle Mancus; Nhan Tran; Jakob Zinsstag; Daniel Cobos Muñoz (BMC, 2021)
Abstract Background One Health approaches such as the Joint human and animal vaccination programmes (JHAVP) are shown to be feasible and to increase health care access to hard-to-reach communities such as mobile pastoralists. However, the financial sustainability and the integration into the public health systems at the district level of such programmes are still challenging. The main objective of the present study was to give insight to the feasibility and financial sustainability of JHAVP integrated as part of the public health system in Chad. Methods We conducted a mixed methods study using semi-structured key informant interviews, focus group discussions and budget impact analysis. Strengths, weaknesses, opportunities, and threats were analysed regarding the feasibility and sustainability of the implementation of JHAVP in Danamadji health district in Chad. Feasibility was further analysed using three dimensions: acceptability, implementation, and adaptation. Financial sustainability of JHAVP was analysed through budget impact analysis of implementation of the programme at district level. Results The acceptability of this approach was regularly assessed by immunization campaign teams through evaluation meetings which included pastoralists. The presence of authorities in the meetings and workshops of the programme had an incentive effect since they represent a mark of consideration these populations generally declared to be lacking. The coordination between the public health and veterinary services at central and decentralized level seemed to be a key element in the success of the implementation of the programme. Regarding financial sustainability, the total incremental budget impact was 27% slightly decreasing to 26% after five years, which accounts for up to one third of the total budget of the district health office. Also, given that most of the costs for each round are recurrent costs, efficiency gains from scale effects over time are limited. Conclusion Based on these findings, we conclude that for JHAVP to be routinely delivered at the district health level, a considerable increase in financial resources would be required. The district could benefit from joint immunization to maintain contact with mobile pastoralists to promote the use of available immunization services at district level.